2012
DOI: 10.1149/2.049302jes
|View full text |Cite
|
Sign up to set email alerts
|

Template-Based Electrodeposition Growth Mechanism of Metal Nanotubes

Abstract: A possible growth mechanism for template-based electrodeposition metal nanotubes was presented. We proposed that the formation of nanotube was a result of kinetics controlling the deposition process, and was related to the crystal structure. According to the mechanism, various nanotubes, such as Zn, Co, Cu, Ni, ZnNi, and CoNi, were fabricated with aluminum oxide templates using a DC electrodeposition method. The deposit morphology dependence of potential was discussed. We further elaborated the feasibility of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…This is in good agreement with Ref. [19]. Thus, we can conclude that the electrodeposition process is dominated by kinetics or thermodynamics when v B v c and v [ v c , respectively.…”
Section: Resultssupporting
confidence: 92%
“…This is in good agreement with Ref. [19]. Thus, we can conclude that the electrodeposition process is dominated by kinetics or thermodynamics when v B v c and v [ v c , respectively.…”
Section: Resultssupporting
confidence: 92%
“…These parameters have been found to influence not only the chemical composition (Vega et al, 2012;Llavona et al, 2013;Moskaltsova et al, 2014) and crystallographic structure (Zhang et al, 2013a;Vivas et al, 2012a) of the deposits, but also the formation of tubular shaped nanostructures (Ponrouch et al, 2010a;Davis and Podlaha, 2005;Narayanan et al, 2008). First of all, the electrolyte solution needs to contain the metal ions of the material one wants to deposit.…”
Section: Influence Of the Electrolyte Solutionmentioning
confidence: 99%
“…The tuning of the applied potential during the electrochemical synthesis of a material will influence the growth rate that will dominate the deposition process Yoo and Lee, 2004;Zhang et al, 2013a;Liu et al, 2008a;Guo et al, 2010). For metals with close-packed crystallographic structures, the growth rate can be determined by the 2-D nucleation rate (v n ), when the process is thermodynamically dominated, or by the propagation rate of monoatomic steps (v p ), when it is kinetically dominated.…”
Section: Different Growth Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9] In addition, PAA with nanopores are popularly used as a template for the synthesis of various nanowires and nanotubes. 10,11 Zhao et al 12 constructed a PAA film embedded with carbon nanotubes (CNTs@PAA) on an Al substrate and found that infusion with water resulted in a significant color change. Such films might be used as water sensors.…”
Section: Introductionmentioning
confidence: 99%